Pengembangan Tanggung Jawab melalui Problem Based Learning Menggunakan Google Classroom pada Materi Aturan Segitiga - Muflichati Nurin Azizah (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
Learning in schools during the Covid-19 pandemic cannot be carried out face-to-face. The use of the internet, cell phones or computers is the main support in delivering materials and tasks to achieve the expected competencies and in conducting assessments. Assessment in the 2013 curriculum is carried out on the aspects of knowledge, skills and attitudes of students. Responsibility is one of the attitudes to be achieved through learning mathematics as stated in Permendikbud Number 37 of 2018 concerning Changes in KI/KD. This study aims to find out how to develop an attitude of responsibility for the triangle rules materials through Problem Based Learning with Google Classroom for class X-MIPA 3 students of SMA Negeri 1 Yogyakarta in the 2019/2020 academic year. The research was conducted in three cycles. Each cycle consists of the planning, action, observation, and reflection stages. The results showed that it could develop students' responsible attitudes. The learning process is carried out by: (a) Giving the prerequisite ability pretest at the orientation phase; (b) Presentation of real-world problems motivates, increases initiative, and focuses on learning; (c) Students are encouraged to learn to develop new knowledge, actively work on group assignments, and be responsible for completing assignments; (d) The opportunity to explore knowledge, develops an attitude of responsibility and improves mathematics learning outcomes; (e) During the learning process, the interest of students in learning the material increases and has a sense of responsibility to do the assigned tasks so as to improve mathematics learning outcomes.